Pelatihan Pemberdayaan Mandiri Bagi Orang Dengan HIV/AIDS (ODHA) Kabupaten Kebumen - Khasanah, Nur; Saryatun; Rizana, Dani (Jurnal Inovasi Pengabdian Masyarakat, 2024)
Self-empowerment activities are a process in which individuals or groups are provided with the knowledge, skills and resources necessary to overcome challenges and improve their quality of life. In the context of people living with HIV/AIDS, independent empowerment is very important because they face various stigmatization and discrimination that can affect their physical, mental and social health. Independent empowerment for people with HIV/AIDS also involves providing life skills. This includes job training, financial skills, and social skills learning. By having these skills, they can increase job opportunities, manage their finances wisely, and build healthy social relationships. The method of implementing activities uses the experiential learning method. The aim of this community service activity is to strengthen the independent empowerment of PLWHA, so that they can help people living with HIV/AIDS to live with dignity, independence and contribute positively to society.